Keiretsu : - Miyashita, Kenichi (McGraw-Hill, 1994)
Two Tokyo-based reporters delve inside Japanese big business to show Westerners the full picture -- and to explain precisely how "Japan Inc." has come to dominate global commerce in modern times. Kenichi Miyashita and David Russell investigate their subject through the fascinating prism of the keiretsu -- Japan's government-sanctioned networks of banks, manufacturers, suppliers, and distributors. Do these syndicates have valuable lessons to teach us? Or do they deserve their rap as protectionist cartels? Or both? Only here will you discover the complete and unbiased truth. And only here will you find haunting, firsthand accounts by Japanese subcontractors of their service to the keiretsu a side of business rarely seen by Westerners.